Trend Penggunaan Aplikasi ELSA Speak pada Era Society 5.0 - Desmiyanti (Universitas Adiwangsa Jambi, 2024)
The Era of Society 5.0 is the era of digital transformation power. The Era of Society 5.0 provides a different perspective for innovation in supporting long-term industry to humanity. One of the technologies present in the era of society 5.0 is the ELSA Speak application which is useful for making it easier for learners to understand and use English. By conducting a theoretical study of research compilation based on systematic observation methods based on data from Science Direct and Springer, it was hoped that this research will be sharper in obtaining in-depth analysis. The results of this study indicated that (1) ELSA Speak helped English speaking skills, users in expanding vocabulary and learning commonly used phrases (2) ELSA Speak helped 1.5 billion language learners worldwide improve their English speaking skills. (3) Its limitations and challenges were this application focused more on pronunciation and lacked in teaching grammar or other aspects of learning English. In addition, the accuracy of voice analysis can be affected by accent or microphone quality. The last, the learners had to spend some money to be able to subscribe The ELSA Pro. Keywords: trend, ELSA Speak, and Society 5.0